1998
DOI: 10.1007/s004420050574
|View full text |Cite
|
Sign up to set email alerts
|

The effects of simulated spring goose grazing on the growth rate and protein content of Phleum pratense leaves

Abstract: The effects of simulated goose grazing on Phleum pratense plants were tested in an Iceland hayfield during the spring goose staging period (19 April-11 May 1997). Plants in an area exclosed from the influence of grazing and the nutrient effects of goose faeces were subject to the removal of the youngest lamina once, three and four times during this period. Clipping three and four times resulted in 25-41% increases in cumulative elongation of youngest laminae compared with unclipped plants. Total cumulative lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
1
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 22 publications
2
29
1
1
Order By: Relevance
“…This is in contrast to other studies that have found vegetation in grazed areas to have higher nitrogen concentrations than in ungrazed areas (e.g., Ydenberg and Prins 1981;Bazely and Jefferies 1985;Day and Detling 1990;Hik and Jefferies 1990;Fox et al 1998;Sirotnak and Huntly 2000). In several of the studies, higher shoot nitrogen concentrations in grazed areas only occurred with the addition of excreta (Bazely and Jefferies 1985;Day and Detling 1990;Hik and Jefferies 1990) and/or when vegetation was grazed multiple times by herbivores (Ydenberg and Prins 1981;Hik and Jefferies 1990;Fox et al 1998). The lack of a grazing effect on plant nitrogen concentrations in our study may possibly be explained by the minimal amounts of excreta added to grazed areas, and the fact that plants are grazed only one time during the growing season.…”
Section: Discussioncontrasting
confidence: 83%
“…This is in contrast to other studies that have found vegetation in grazed areas to have higher nitrogen concentrations than in ungrazed areas (e.g., Ydenberg and Prins 1981;Bazely and Jefferies 1985;Day and Detling 1990;Hik and Jefferies 1990;Fox et al 1998;Sirotnak and Huntly 2000). In several of the studies, higher shoot nitrogen concentrations in grazed areas only occurred with the addition of excreta (Bazely and Jefferies 1985;Day and Detling 1990;Hik and Jefferies 1990) and/or when vegetation was grazed multiple times by herbivores (Ydenberg and Prins 1981;Hik and Jefferies 1990;Fox et al 1998). The lack of a grazing effect on plant nitrogen concentrations in our study may possibly be explained by the minimal amounts of excreta added to grazed areas, and the fact that plants are grazed only one time during the growing season.…”
Section: Discussioncontrasting
confidence: 83%
“…Effects of human disturbance (deliberate or otherwise) at restricted spring stopovers is having an impact at the population level and is a major complication in management aimed at setting defined limits on goose numbers (Calvert and Gauthier 2005). Evidence that the temporal and spatial pattern of grazing by geese at spring stopovers may have positive effects on their own food supply on the short-term (Fox et al 1998; Van der Graaf et al 2005 underlines the vulnerability of this 'fine-tuning' to external disturbance or other agents of change such as climate trends (Prop et al 1998;Tøttrup et al 2006, for an extensive overview see Møller et al 2004).…”
Section: Migratory Connectivity and Conservationmentioning
confidence: 99%
“…However, it is only in the last 60 years that extensive creation of dry hayfields and the draining of wetlands has taken place on a large scale in a manner likely to affect the White-fronted Geese (Francis & Fox 1987). In recent decades, spring staging Greenland Whitefronted Geese in Iceland have increasingly used managed grasslands for food (Fox et al 1998(Fox et al , 1999b and their reliance on wetlands has decreased. Nevertheless, since farms were associated with wetlands (which in former times provided food for over-wintering livestock in the form of hay made from Carex lyngbyei), the creation of grass-sward hayfields in the vicinity of farms provides an alternative source of food for geese with established patterns of use for roost and feeding areas.…”
Section: Discussionmentioning
confidence: 99%